2013
DOI: 10.1186/1472-6920-13-96
|View full text |Cite
|
Sign up to set email alerts
|

A year in transition: a qualitative study examining the trajectory of first year residents’ well-being

Abstract: BackgroundIt is generally understood that trainees experience periods of heightened stress during first year residency, yet there is little information on variations in stress and well-being over the transition period or those factors that contribute to these variations. This qualitative study explored the trajectory of well-being described by first year residents in the context of challenges, supports and adaptations over time.MethodsIn-depth interviews were conducted face-to-face with 17 first year residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 29 publications
9
83
0
2
Order By: Relevance
“…Os níveis de ansiedade e depressão apresentados pelos residentes em Pediatria deste estudo evidenciam que o período de transição aluno-profissional é desgastante, reforçando os resultados de outros estudos com médicos residentes 8,9,12,13,17,19 . Um estudo com residentes canadenses apontou que a presença de transtornos psicológicos é maior no primeiro ano de formação, quando os profissionais estão em fase de adaptação à nova rotina de trabalho e, por conta disso, apresentam maior insegurança 20 .…”
Section: Discussionunclassified
“…Os níveis de ansiedade e depressão apresentados pelos residentes em Pediatria deste estudo evidenciam que o período de transição aluno-profissional é desgastante, reforçando os resultados de outros estudos com médicos residentes 8,9,12,13,17,19 . Um estudo com residentes canadenses apontou que a presença de transtornos psicológicos é maior no primeiro ano de formação, quando os profissionais estão em fase de adaptação à nova rotina de trabalho e, por conta disso, apresentam maior insegurança 20 .…”
Section: Discussionunclassified
“…25,36,37 However, there seem to be missed opportunities for junior doctors and medical students to be able to openly discuss the impact of a patient death and debrief within the acute care context. 25 Whilst palliative care attachments provided an open space for debriefing, inside the hospital, the study participants did not seek or find opportunities to discuss these issues with senior medical staff and preferred to talk to their own families.…”
Section: Discussionmentioning
confidence: 99%
“…Interns identified that lighter rotations and vacations were associated with upswings in their well-being, and long work hours and on call were associated with downswings. 24 Obstetrics-gynecology residents in 1 program rated their lifestyle low, which correlated with lower residency satisfaction. 22 Being in a relationship was studied and found associated with greater well-being.…”
Section: Factors Correlated With Resident Well-beingmentioning
confidence: 99%
“…Specifically, a sense of control and autonomy, pursuit and achievement of goals, opportunities for learning, increased confidence and sense of increasing mastery, positive feedback, and positive colleague relationships were all associated with greater well-being across 4 studies. [21][22][23][24] A few additional factors were associated with wellbeing. Sleep was found to be important in several studies.…”
Section: Factors Correlated With Resident Well-beingmentioning
confidence: 99%